Enforcement of Intellectual Property Rights at Custom Checkpoints: An Analysis of Various Jurisdictions - Singh, Kanwal DP (Kathmandu School of Law Review, 2019)
The vitals of modern economic growth is dependent on fair and free trade. Any economic and fiscal improvement requires wide and rampant foreign investment and in absence of any credible and concrete law for the protection of invention, trade secrets, patent or for that matter the trademark/brand, the scheme of foreign investment cannot be successful, which in turn jeopardizes the national, economic, social and scientific growth. Border customs agencies world over are an important arm of governments that play a vital role in the protection of Intellectual Property ("IP") rights. The research looks into the Indian framework for the protection of Intellectual Property Rights ("IPR") at custom checkpoints i.e. Intellectual Property Rights (Imported Goods) Enforcement Rules, 2007. It also analyzes the processes in different jurisdictions to judge whether they are better equipped to deal with piracy. The shortcomings of the Indian law are ascertained and suggestions are made for better enforcement.